Romanticism and Caricature - Haywood, Ian (Cambridge : Cambridge University Press, 2013)
Ian Haywood explores the 'Golden Age' of caricature through the close reading of key, iconic prints by artists including James Gillray, George and Robert Cruikshank, and Thomas Rowlandson. This approach both illuminates the visual and ideological complexity of graphic satire and demonstrates how this art form transformed Romantic-era politics into a unique and compelling spectacle of corruption, monstrosity and resistance. New light is cast on major Romantic controversies including the 'revolution debate' of the 1790s, the impact of Thomas Paine's 'infidel' Age of Reason, the introduction of paper money and the resulting explosion of executions for forgery, the propaganda campaign against Napoleon, the revolution in Spain, the Peterloo massacre, the Queen Caroline scandal, and the Reform Bill crisis. Overall, the volume offers important new insights into the relationship between art, satire and politics in a key period of history.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Romanticism; Caricature in literature